PREPONDERANCE OF EOSINOPHILIA AT TERTIARY CARE CENTRE IN THE SOUTHWEST REGION OF PATNA: A RETROSPECTIVE CROSS-SECTIONAL STUDY - Sukriti, MD; Md Abdullah; Ravish, Kumar; Chakrabarti, Sudipta (Student’s Journal of Health Research Africa, 2024)
Background Eosinophils are synthesized in response to inflammation in the body. The underlying disease can vary to a large extent. The data regarding the underlying causes is scarce. Objectives To determine the eosinophilia cases at the tertiary care center of the Southwest Region of Patna. Materials and Methods The present retrospective, observational, and hospital-based study was conducted. The blood samples of the patients participating in the study were tested for complete blood count on a hematology analyzer. The manual identification of the WBC and determination of the AEC was carried out on the blood samples. The demographic and clinical details of the patients were recorded and statistically analyzed. Results A total of 301 patients were reported to have eosinophilia. Of these, 203 (67.4%) were male, and 98 (32.6%) were female. The present study showed higher cases of eosinophilia in male patients. 13.6% of the participants with eosinophilia were within the age group of 21-30 years. 91.4% of the cases were under the moderate eosinophilia category. The majority of the patients had agriculture as their occupation. Conclusion In conclusion, the present study has detected that eosinophilia is frequent in the West Region of Patna. A thorough search for the etiological factors and other relevant investigations is essential for appropriate management. Recommendation Eosinophilia can be associated with various etiological factors. It is essential to determine the underlying cause to treat eosinophilia.